Polymer/bioactive glass nanocomposites for biomedical applications: A review - Boccaccini, Aldo R.; Erol, Melek; Stark, Wendelin J.; Mohn, Dirk; Hong, Zhongkui; Mano, Joao F. (Composites Science and Technology, 2010)
Nanoscale bioactive glasses have been gaining attention due to their reported superior osteoconductivity when compared to conventional (micron-sized) bioactive glass materials. The combination of bioactive glass nanoparticles or nanofibers with polymeric systems enables the production of nanocomposites with potential to be used in a series of orthopedic applications, including scaffolds for tissue engineering and regenerative medicine. This review presents the state of art of the preparation of nanoscale bioactive glasses and corresponding composites with biocompatible polymers. The recent developments in the preparation methods of nano-sized bioactive glasses are reviewed, covering sol-gel routes, microemulsion techniques, gas phase synthesis method (flame spray synthesis), laser spinning, and electro-spinning. Then, examples of the preparation and properties of nanocomposites based on such inorganic bionanomaterials are presented, obtained using various polymer matrices, including polyesters such as poly(hydroxybutyrate), poly(lactic acid) and poly(caprolactone), and natural-based polymers such as polysaccharides (starch, chitin, chitosan) or proteins (silk fibroin, collagen). The physico-chemical, mechanical, and biological advantages of incorporating nanoscale bioactive glasses in such biodegradable nanocomposites are discussed and the possibilities to expand the use of these materials in other nanotechnology concepts aimed to be used in different biomedical applications are also highlighted. © 2010 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.polyme
Keywords: A. Bioactive glass; A. Nanocomposites; A. Nanoparticles; A. Particle-reinforced composites; B. Porosity/voids